Effect of Shoes With Toe Rocker Angles of 10 and 15 Degrees Compared to Control Shoes on Plantar Pressure, Force and Contact Surface in Healthy Older Adults: A Clinical Trial - Najmeh Bagheriankhuzani; Mahmood Bahramizadeh; Atefeh Aboutrabi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives: The present study aims to investigate the effect of shoes with toe rocker angles of 10 and 15 degrees, compared to control shoes, on the plantar pressure distribution, force, and contact surface in healthy older adults to help maintain the independence and function of the elderly and prevent possible injuries. Methods & Materials: In this clinical trial, 35 healthy older adults (15 males and 20 females) with mean age of 65.2±4.37 years, who were selected using a convenience sampling method from those with no lower limb deformity, no orthopedic and neurological diseases, and with ability to walk without assistance devices. Three types of shoes were used including traditional shoes as controls, shoes with a toe rocker angle of 10 degrees, and shoes with a toe rocker angle of 15 degrees. The maximum plantar pressure in eight anatomical areas were measured using the Pedar system. Repeated measures ANOVA was used for data analysis. Results: There was no significant difference in pressure distribution (P>‌0.05), force (P>‌0.05) and contact surface (P>‌0.05) in eight anatomical areas of the sole of the feet between the three study groups. Conclusion: It seems that the use of shoes with toe rockers do not affect the plantar pressure distribution, force and contact surface in older adults. These shoes can be used without the fear of changing the plantar pressure distribution and causing pain and injury in the elderly.